The Determinants Affecting Environmental Disclosure in the High Profile Companies in Indonesia - Junita, Niken Lady; Yulianto, Agung (Accounting Analysis Journal, 2018)
This study aims to analyze whether the board of commissioners, managerial ownership, media coverage, firm size, and profitability can affect the disclosure of the environment. The population of this study is a high profile company listed on the Indonesia Stock Exchange in 2011-2015 as many as 83 companies. This research used purposive sampling method and elected 11 companies as sample with 55 unit of analysis. The results show that board of commissioners, media coverage, and company size have a positive effect on environmental disclosure. However, managerial ownership and profitability cannot affect the disclosure of the environment. The conclusions of this study are factors that proved to have a positive effect on the disclosure of the environment are board of commissioners, media coverage, and company size.